PENGARUH DUALITAS CEO DAN KEPEMILIKAN ASING TERHADAP PRAKTIK PELAPORAN BERKELANJUTAN: Fungsi Internal Audit sebagai variabel moderasi - Dina Rosari (Lembaga Penelitian Universitas Trisakti, 2020)
This study uses a research model to obtain empirical evidence about the effect of CEO Duality and foreign ownership on Sustainability Report moderated by Internal Audit Function. The variables used in this research model are the number of sustainability disclosure, CEO duality and foreign ownership and internal audit. The research sample consisted of LQ45 company that listed on the Indonesia Stock Exchange in the period 2016 - 2018. Based on sampling using the purposive sampling method, the samples used in this study were 45 companies with a three-year period producing 135 sample units. Data analysis was performed by multiple linear regression analysis with the OLS (Ordinary Least Square) estimation method or the Smallest Square Method for time series data. R square adjusted value is already above 50 percent more, so the model is considered good enough. If seen above is the result of the coefficient of determination, the Adjusted R Square value of 0.6848 so this shows that the total independent variable is able to explain variation and contribute to the dependent variable that is equal to 68.48 percent and the rest by other variables outside the model.